Break in the Stroke Chain of Survival due to COVID-19. Issue 8 (August 2020) - Montaner, Joan; Barragán-Prieto, Ana; Pérez-Sánchez, Soledad; Escudero-Martínez, Irene; Moniche, Francisco; Sánchez-Miura, José Antonio; Ruiz-Bayo, Lidia; González, Alejandro
Abstract : Background and Purpose: Emergency measures to treat patients with coronavirus disease 2019 (COVID-19) and contain the outbreak is the main priority in each of our hospitals; however, these measures are likely to result in collateral damage among patients with other acute diseases. Here, we investigate whether the COVID-19 pandemic affects acute stroke care through interruptions in the stroke chain of survival. Methods: A descriptive analysis of acute stroke care activity before and after the COVID-19 outbreak is given for a stroke network in southern Europe. To quantify the impact of the pandemic, the number of stroke code activations, ambulance transfers, consultations through telestroke, stroke unit admissions, and reperfusion therapy times and rates are described in temporal relationship with the rising number of COVID-19 cases in the region. Results: Following confinement of the population, our stroke unit activity decreased sharply, with a 25% reduction in admitted cases (mean number of 58 cases every 15 days in previous months to 44 cases in the 15 days after the outbreak, P <0.001). Consultations to the telestroke network declined from 25 every 15 days before the outbreak to 7 after the outbreak ( P <0.001). The increasing trend in the prehospital diagnosis of stroke activated by 911 calls stopped abruptly in the region, regressing to 2019 levels. The mean number of stroke codes dispatched to hospitals decreased (78% versus 57%, P <0.001). Time of arrival from symptoms onset to stroke units was delayed >30 minutes, reperfusion therapy cases fell, and door-to-needle time started 16 minutes later than usual. Conclusions: The COVID-19 pandemic is disruptive for acute stroke pathways. Bottlenecks in the access and delivery of patients to our secured stroke centers are among the main challenges. It is critical to encourage patients to continue seeking emergency care if experiencing acute stroke symptoms and to ensure that emergency professionals continue to use stroke code activation and telestroke networks.